Top‐down control by Harmonia axyridis mitigates the impact of elevated atmospheric CO2 on a plant–aphid interaction. (27th May 2014) - Hentley, William T.; Hails, Rosemary S.; Johnson, Scott N.; Hefin Jones, T.; Vanbergen, Adam J.
Abstract The present study investigated the impact of elevated atmospheric CO2 (390 or 650 µmol/mol) on raspberry genotypes varying in resistance to the large raspberry aphid Amphorophora idaei and any subsequent impact on the coccinellid predator Harmonia axyridis. CO2 enrichment promoted plant growth, ranging from 30% in the partially susceptible cultivar to a more than 100% increase for the susceptible cultivar. Aphid abundance and colonization (presence–absence) on the susceptible cultivars were not influenced by CO2 enrichment. On the resistant cultivar, aphid colonization increased from 14% in ambient CO2 to 70% in elevated CO2 with a subsequent increase in aphid abundance, implying a breakdown in resistance. Inclusion of the natural enemy on the resistant cultivar, however, suppressed the increase in aphid abundance at elevated CO2. The present study highlights how crop genotypes vary in responses to climate change; some cultivars can become more susceptible to aphid pests under elevated CO2. We do, however, demonstrate the potential for top‐down control to mitigate the effect of global climate change on pest populations.